(untitled) (Dordrecht, Netherlands, 1995)
The subsistence agriculture of the pre-chemical era efficiently sustained the nitrogen status of soils by maintaining a balance between N loss and N gain from biological nitrogen fixation (BNF): the microbial conversion of atmospheric N to a form usable by plants. This was possible with less intensive cropping, adaptation of rational crop rotations and intercropping schemes, and the use of legumes as green manure. Modern agriculture concentrates on maximum output, however, overlooking input efficiency; It is not sustainable. Intensive monocropping, with no or inadequate crop rotations or green manuring, together with the excessive use of chemical N fertilizers, results in an imbalance between N gain and N loss. The losses are often larger than the gains, and soil N status declines. The challenge is to sustain soil N fertility in many different tropical and temperate farming systems operating at high productivity levels. This requires judicious integration of BNF components, maintaining a good balance between N losses and gains. In this book, papers on BNF in crop forage and tree legumes are augmented with discussions of integrated farming systems involving BNF, soil and N management, and recycling of legume residues. BNF by non-legumes are discussed, and attempts to transform cereals into nodulating plants are critically reviewed. Advances in the development of novel methodologies to understand symbiotic relations and to assess N2 fixation in the field are described, and means are presented to enhance BNF through plant and soil management or breeding and selection. Problems encountered in exploiting BNF under field conditions are examined, as are promising approaches to improving BNF exploitation.
Keywords: Nitrogen in agriculture,Nitrogen,Cropping systems,Sustainable agriculture; Congresses,Fixation,Congresses,Congresses,Congresses